2022
DOI: 10.1021/acsami.2c14688
|View full text |Cite
|
Sign up to set email alerts
|

Band Structure and Phonon Transport Engineering Realizing Remarkable Improvement in Thermoelectric Performance of Cu2SnSe4 Incorporated with In2Te3

Abstract: Cu2SnSe4 (CTS) ternary chalcogenides have potential applications in thermoelectrics for they crystallize in a high-symmetry cubic structure and consist of earth-abundant and eco-friendly elements. However, the pristine CTS does not have optimal thermoelectric (TE) performance (ZT = 0.35 at ∼700 K), so further investigation is required in this regard. In this work, we propose an incorporation of In2Te3 with a defect zinc-blende cubic structure into CTS, aiming to regulate the electronic and phonon transport mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…That is why we observed a big drop in mobility at x = 0.05 (see Figure 3b). Although the interstitial In atom in CTS has the potential to reduce the mobility as well due to the band convergence, according to the previous investigation, [ 33 ] the activation energy ( E A ) rapidly decreases from 22 m eV ( x = 0.05) to 1.2 m eV ( x = 0.2) with an increase in x , estimated according to the slope of each straight line in Figure 5a,b. This suggests that the localized bondage to the carrier weakens and the transport between the electron and phonon decouples rapidly.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…That is why we observed a big drop in mobility at x = 0.05 (see Figure 3b). Although the interstitial In atom in CTS has the potential to reduce the mobility as well due to the band convergence, according to the previous investigation, [ 33 ] the activation energy ( E A ) rapidly decreases from 22 m eV ( x = 0.05) to 1.2 m eV ( x = 0.2) with an increase in x , estimated according to the slope of each straight line in Figure 5a,b. This suggests that the localized bondage to the carrier weakens and the transport between the electron and phonon decouples rapidly.…”
Section: Resultsmentioning
confidence: 78%
“…Whereas the conventional band transport mechanism should not have such a big impact on μ. [33] The electrical properties of the materials (Cu 2 Sn 1Àx In x Se 4 ) (x ¼ 0-0.2) are presented in Figure 6 as a function of temperature. It is observed that the Seebeck coefficients (α) are all positive, indicating that the majority of carriers are holes.…”
Section: Te Performancementioning
confidence: 99%
“…In the meantime, the authors found that p-type doping on the Sn site has little influence on the upper valence band (VB), according to those observed in Cu 2 SnSe 3 systems. We noticed that in the band structure of CSS, its Fermi level (Fr) is in the deep part of the valence band . What should be further noted is that there is also an energy gap (∼0.5 eV) above Fr with the bonding states partially non-occupied. , In this regard, the structure of CSS, unlike those of Cu 2 SnSe 3 , , Cu 2 SnSe 4 , and other Cu-containing chalcogenides, , might be favorable to the regulation of the conduction band (CB) if proper dopants are incorporated.…”
Section: Introductionmentioning
confidence: 83%
“…This is because the element In (Te) is energetically favorable to reside at the Sn (Se) site. 10,13 On the other hand, the binary In 2 Te 3 or Ga 2 Te 3 having its inherent structural vacancy 14−16 is often used as a dopant to tune the carrier concentration of materials, similar to those observed in InSb, 17 (Sn,Ge)Te, 18,19 CuGaTe 2 , 20 significantly than the single element In or Te does. It is thus effective to regulate both the phonon and electronic transport mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation